Pemberdayaan Kelompok Usaha Ikan Kering dalam Meningkatkan Ekonomi Keluarga - Hidayatun Nisa; Ashaluddin Jalil; Rd. Siti Sofro Sidiq (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2022)
The economy of coastal communities which are dominated by underprivileged families should be improved for the better through empowering business groups by utilizing the resources in their environment. This study aims to determine the empowerment of the Dried Fish Business group in improving the family economy. The method used is qualitative research with sampling using purposive sampling. The results of the study found that the empowerment and follow-up carried out by the government were still maximal for the Penempol Dried Fish business group, the utilization of human and natural resources was not optimal and the results of the business group had not been able to improve the family economy but were only able to meet daily needs.